2021
DOI: 10.1111/1745-9125.12289
|View full text |Cite
|
Sign up to set email alerts
|

Can the group disincentivize offending? Considering opt‐out thresholds and decision reversals*

Abstract: Scholars generally agree that offending decisions occur in social context, with some suggesting that choice models should explicitly integrate the notion that the deviant actions of others can incentivize offending. In this study, we investigate whether group settings can also disincentivize deviant action via reverse bandwagon effects, where individuals reverse their offending decision and express an intention to opt out of the criminal act. Based on survey data from three universities using hypothetical scen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…Consistent with evidence demonstrating non-linear peer effects, it is possible that the role individuals occupy is more salient in structuring responsibility in smaller groups, however, among larger group sizes there may be limited differences in how responsibility is perceived across roles (e.g., Zimmerman and Messner 2011). McGloin et al (2021) uncovered how the presence of others across scenarios with divergent group sizes impacted participation in group offending and attributed this finding to meaningful differences in perceived rewards and costs. Thus, the effect of one's role on perceived responsibility—as an informal cost associated with crime—may be viewed quite differently depending on the size of the group.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with evidence demonstrating non-linear peer effects, it is possible that the role individuals occupy is more salient in structuring responsibility in smaller groups, however, among larger group sizes there may be limited differences in how responsibility is perceived across roles (e.g., Zimmerman and Messner 2011). McGloin et al (2021) uncovered how the presence of others across scenarios with divergent group sizes impacted participation in group offending and attributed this finding to meaningful differences in perceived rewards and costs. Thus, the effect of one's role on perceived responsibility—as an informal cost associated with crime—may be viewed quite differently depending on the size of the group.…”
Section: Discussionmentioning
confidence: 99%
“…But the more rule violations become prevalent, the more they are likely to switch from rule-abiding to rule-violating themselves (McGloin and Rowan 2015; also see McGloin and Thomas 2016b). Based on the concept of delinquency balance (McGloin 2009), it has further been suggested that there might not only be a lower bound of peer criminal activity, necessary for engaging in crime, but also an upper bound, leading to desistance from crime (McGloin et al 2021: 739).…”
Section: Extensionsmentioning
confidence: 99%
“…They found that with more hypothesized co-offenders, perceptions of formal and informal costs to the actor from joining decreased, whereas the anticipated rewards, such as fun and social inclusion, increased. In a recent refinement, McGloin et al (2021) identified an "opt-out threshold" or reverse bandwagon effect, where potential co-offenders can become so numerous as to increase perceptions of risks and costs and discourage (co)offending.…”
Section: Social Context For Offending Decisionsmentioning
confidence: 99%